A dual-functional UiO-66/TiO2 composite for water treatment and CO2 capture. Issue 26 (14th March 2017) - Wang, Yang; Liu, Huijin; Zhang, Manling; Duan, Wubiao; Liu, Bo
Abstract : UiO-66/TiO2 composites were fabricated via self-assembly using a solvothermal method. Abstract : UiO-66/TiO2 composites were fabricated via self-assembly using a solvothermal method. The composites exhibits high efficiency and stability for removing rhodamine B and methyl blue under strongly acidic conditions via a simple regeneration process. The participation of the UiO-66 structure in TiO2 was found to reduce the electron–hole recombination but did not change its adsorption ability on dyes, which leads to its enhanced photocatalytic properties under visible light radiation. In addition, the introduced TiO2 in MOFs was firstly found to increase the number of active sites, which is beneficial for CO2 capture. Therefore, it can be suggested that porous MOFs combined with photoactive semiconductors may introduce a new class of dual-functional materials for use in water treatment and CO2 capture.